Under Suspicion: Trust Dynamics with Secret Undermining. (20th June 2022) - Kolb, Aaron; Madsen, Erik
Abstract: We study how an organization should dynamically screen an agent of uncertain loyalty whom it suspects of committing damaging acts of undermining. The organization controls the stakes of the relationship, while the agent strategically times undermining, which can occur repeatedly and is detected only stochastically. The optimal commitment stakes policy exhibits both discreteness and gradualism, with distinct "untrusted" and "trusted" phases featuring gradually rising stakes during the untrusted phase and a discrete gap in stakes between phases. This policy is also the equilibrium outcome when the organization cannot commit, and the agent's equilibrium undermining policy exhibits variable, non-monotonic intensity.